(3TQM OjhGf GdeJfHis - (3CHh GdMSf Ydj Hf CMeO GdhGMOis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi ShGHZ GdfYe (B,(3HYO aEf GdTYQ CHbi cdGe hEf GdfGS efP YUQ bOje bO hdhG LejY GdCTYGQ UaMI GdEYQGV s
(3BNQgG (B:s
(3gPG cdGeg ai gPG GdHjJ ai cJGHg GdJLfi hGdaQL , hgh UMjM hGdeYfi eG bGdg , hGdQhGjI GdUMjMI HaJM GdWGA Je TQM OjhGf CHj GdWjH ddEeGe GdhGMOi HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3cJH GdTYQ ajgG HGdMeQIs
(3Ydi GdfSNI JedcGJ eMOKI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs